1996
DOI: 10.1179/mst.1996.12.9.717
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallisation and texture in hot deformed aluminium alloy 7010 thick plates

Abstract: The recrystallisation behaviour and its effect on the crystallographic texture during solution heat treatment of thick aluminium alloy 7010 plates has been studied both on commercially hot rolled plates and on laboratory specimens deformed in plane strain compression. In addition to X-ray macrotexture analysis, individual grain orientation measurements within the recovered subgrains and the recrystallised new grains were performed by means of electron backscattering diffraction. Significant recrystallisation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This effect of texture sharpening upon recovery in Al alloys has already been described earlier 27 and is attributed to a clean-up of the subgrain structure accompanied by a reduction in average misorientation between adjacent subgrains. 28 The evolution of the substructure during back annealing was studied in more detail by TEM. Figure 7 contains TEM bright field images of the substructure in the as deformed and two back annealed samples.…”
Section: Resultsmentioning
confidence: 99%
“…This effect of texture sharpening upon recovery in Al alloys has already been described earlier 27 and is attributed to a clean-up of the subgrain structure accompanied by a reduction in average misorientation between adjacent subgrains. 28 The evolution of the substructure during back annealing was studied in more detail by TEM. Figure 7 contains TEM bright field images of the substructure in the as deformed and two back annealed samples.…”
Section: Resultsmentioning
confidence: 99%
“…The dispersoid precipitation in 7xxx Al-Zn-Mg-Cu alloys has been extensively investigated both experimentally and theoretically in the past years [14,28,29,[57][58][59]. It can be concluded that the improved dispersoid distribution can be achieved through refining the homogenisation conditions and modify the contents of the Zr, Mn, Sc etc., dispersoid-forming elements.…”
Section: Multi-step Homogenisationmentioning
confidence: 99%
“…Combined experiment and finite element simulation have shown the position of maximum shear texture development to lie 80% of the distance from the centerline to the surface [15]. Such gradients in texture have been observed in 7010 plate, with the centerline bearing components typical of plane strain compression and, closer to the surface, a transition to a texture with {001} 110 as the dominant component [16].…”
Section: Crystallographic Texturementioning
confidence: 99%
“…In a detailed study of 7010 plate, Engler et al [16] provide evidence that the recrystallized texture contains a random component associated with particle stimulated nucleation (PSN), while recovery of subgrain structure tends to sharpen the original deformation texture. As indicated above, Zr addition to the alloy suppresses development of recrystallization components.…”
Section: Crystallographic Texturementioning
confidence: 99%
See 1 more Smart Citation